Respuestas

2014-01-29T21:42:26+01:00
Tienes que buscar el término común y luego factorizar:
1 a²+ab+ax+bx
a(a+b) + x(a+b)
= (a+x)(a+b)
2  am-bm+an-bn
m(a-b) + n(a-b(
= (m + n)(a-b)
3 ax-2bx-2ay+4by
ax - 2ay - 2bx + 4by
a(x - 2y) -2b(x - 2y)
=(a-2b)(x-2y)
4 x²-a²+x-a²x
x² + x - a² - a²x
x(x + 1 ) -a²(x + 1)
=( x - a²)(x+1)
5 x+x²-xy²-y²
x(1+x) -y²(x + 1)
=(x-y²)(x+1)
 
6 4a³x-4a²b+3bm-3amx
4a²(ax - b) - 3m( ax - b)
=(4a² - 3m)(ax-b)

7 6ax+3a+1+2x
3a(2x + 1 ) + 1(1+2x)
=(3a+1)(2x+1)


8 3abx²-2y²-2y²+3aby² <- esta mal escrito el ejercicio.
             -4y².

Sl2